KEPENTINGAN JEPANG MENGADAKAN KERJASAMA INSTALASI PENGENDALIAN LIMBAH CAIR DI KAWASAN DANAU TOBA DENGAN BADAN LINGKUNGAN HIDUP SUMATERA UTARA TAHUN 2013 – 2014 - Hendra Sihombing; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research discusses about Japan Interest Conducted Waste Water Cooperation With Environmental Official Of North Sumatera At Lake Toba On 2013 – 2014. This cooperation conducted by implemented kind of technology of Japan was Johkasou. The cooperation was happened because of Japan have special interest on economic and politic over lake Toba through Johkasou. This research used research eksplanation method because the researcher was used hypotesis in this research. Eksplanation reseach methods was used to analys corelation among variables of hypotesis. Technique to collect data were using field research and library research. Field research conducted by interviews with Consul General of Japan in city of Medan, Supervisor of Waste Water of Environmental Official of North Sumatera, and The Head Department of Waste Water of Environmental Official of North Sumatera. The rest data were collected from news, internet, magazine and journal. The researcher used international cooperation theory by Joseph Greico. The result of this research conclude that Japan Interest Conducted Waste Water Cooperation With Environmental Official Of North Sumatera Around of Lake Toba at 2013 – 2014 were Japan economic interest to extend the market of Johkasou trading, Japan political interest to harmonized friendship with Environmental Official of North Sumatera, Japan interest to build the image of technology of Johkasou in front of Indonesian society.Keywords: Economic Politic Interest, Johkasou, International Cooperation